The Influence of the Problem Based Learning Model on Islamic Religious Education Learning Outcomes at SDN 08 Koto Berapak Pesisir Selatan - Sumiarti Sumiarti; Firli Amanda Putri (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This research was motivated by the problems faced by students in understanding how to solve problems in Islamic religious education lessons, because the learning process still focuses on the teacher and students are not actively involved. This situation has an impact on low student learning outcomes. The problem formulation is whether there is a significant effect of the Problem-Based Learning (PBL) Model on the Learning Outcomes of Islamic Religious Education for Grade V Students at SDN 08 Koto Berapak Pesisir Selatan. The purpose of this study is to identify the impact of the Problem-Based Learning (PBL) Model on the Islamic Religious Education Learning Outcomes of Grade V Students at SDN 08 Koto Berapak Pesisir Selatan. This study is quantitative in nature with a quasi-experimental approach, using a one-group pre-test post-test design. The subjects in this study include one class. This study involved one class, namely the fifth grade of SDN 08 Koto Berapak Pesisir Selatan. Data collection methods were conducted through tests and documentation. Based on the analysis of the research results and data processing, the t-value was -3.979 and the t-table was 2.179, which is -3.979 > 2.179, so Ho was rejected. Thus, it can be concluded that there is an effect of the Problem-Based Learning (PBL) Model on the Islamic Education Learning Outcomes of Grade V Students at SDN 08 Koto Berapak Pesisir Selatan.